Analysis of x-ray radiation exposure safety in the radiology installation of Panti Nugroho Hospital Sleman - Iqna, Purwitasari; Anshor, Nugroho; Asih Puji, Utami (Faculty of Medicine, 2026)
Radiology plays a vital role in early diagnosis and risk assessment through real-time imaging. However, ensuring radiation safety is essential to protect patients, healthcare workers, and the public from excessive ionizing radiation exposure. This study aims to analyze the safety of X-ray radiation exposure in the Radiology Installation of Panti Nugroho Hospital, Sleman